The rules of persuasion - Alvarenga, Carlos A. (Ascent Audio, 2023)
Have you ever wondered what makes someone convincing or why some messages persuade when others do not? Have you ever struggled with how to create a persuasive message, story, or presentation? Do you want to understand how persuasion can be used to corrupt or to achieve dangerous ends? The Rules of Persuasion not only explains exactly how persuasion works in all forms of human communication, but it also presents a clear and effective model you can use to put the elements and chemistry of persuasion to work for you in your personal and professional lives. Using insights and examples from art to history to literature to hip-hop, author Carlos Alvarenga updates and expands ideas first presented in Aristotle's Rhetoric, adding original observations regarding the role of the audience in persuasion, persuasion in social media, as well as what happens when the rules of persuasion are used to deceive and corrupt audiences-even entire nations.